A systematic component of the jump-risk premium in an AJD model - Maya, Livio Cuzzi (2015)
We develop an affine jump diffusion (AJD) model with the jump-risk premium being determined by both idiosyncratic and systematic sources of risk. While we maintain the classical affine setting of the model, we add a finite set of new state variables that affect the paths of the primitive, under both the actual and the risk-neutral measure, by being related to the primitive's jump process. Those new variables are assumed to be commom to all the primitives. We present simulations to ensure that the model generates the volatility smile and compute the 'discounted conditional characteristic function'' transform that permits the pricing of a wide range of derivatives.